1987
DOI: 10.1111/j.1365-2621.1987.tb06585.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Constituents of Beef as Influenced by Forage‐ and Grain‐Feeding

Abstract: Hereford yearling steers (N= 144) were alloted to one of three pasture systems: tall fescue, smooth bromegrass-red clover or orchardgrassred clover. After the grazing period, steers were finished in drylot and then serially slaughtered at 0, 56, 84 and 112 days. Carcass quality grades and yield grade numbers increased when steers were fed grain up to 112 days. Tenderness of loin steaks increased up to 84 days, after which no improvements were observed. Sensory panel scores for grassy flavor of steaks and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 25 publications
11
107
1
1
Order By: Relevance
“…Grass fed beef has been reported by U.S. consumers to have less acceptance for beef flavor due to off-flavors (Duckett et al, 2013). Despite previous evidence of a reduction of "grassy" off-flavor from including grain in the animal diet (Larick et al, 1987), in our study no differences in flavor liking scores were observed between HSC and HDP, whereas HCF was more liked than either.…”
Section: Consumer Flavor Likingcontrasting
confidence: 55%
“…Grass fed beef has been reported by U.S. consumers to have less acceptance for beef flavor due to off-flavors (Duckett et al, 2013). Despite previous evidence of a reduction of "grassy" off-flavor from including grain in the animal diet (Larick et al, 1987), in our study no differences in flavor liking scores were observed between HSC and HDP, whereas HCF was more liked than either.…”
Section: Consumer Flavor Likingcontrasting
confidence: 55%
“…The flavour identified as sweet when animals are out to pasture decreases at the expense of the typical flavour of steers. Furthermore, the products of fat degradation (such as aldehydes and cetones) are more apparent in the volatile fraction of meat from grass-fed young bulls than from grain-fed animals [56]. The terpenoids are also less abundant in meat from grain-fed bulls and their contents in meat are associated with various flavours.…”
Section: Auto-oxidation Of Fats At Low Temperaturementioning
confidence: 89%
“…Neutral lipids (mainly triglycerides) of muscles mainly incorporate PUFA as C18:2n-6 and C18:3n-3. Polar lipids (phospholipids) are less selective and incorporate not only C18:2n-6 and C18:3n-3, but also their counterparts (C20:3; C20:4; C22:5) [56].…”
Section: Effects Of Ruminant Feeding On the Nutritional Value Of Meatsmentioning
confidence: 99%
“…[13][14][15]34,35 The n-alkanes, being inert throughout the digestive tract, are commonly used as markers for the estimation of intake, digestibility, and diet composition in grazing animals. 36,37 As for the fatty acid phytyl esters, as reported in our previous paper, 11 two reasonable hypotheses can be formulated: direct transfer from grass, because they had been detected in vegetable matrices, and/or endogenous (rumen or mammary cells) esterification product between fatty acids and free (E)-phytol, which is the main isomer naturally occurring in the chlorophyll molecule.…”
Section: ■ Results and Discussionmentioning
confidence: 99%